Pengaruh Pijat Oketani terhadap Produksi ASI pada Ibu Menyusui di Kabupaten Bantaeng - Husnul Khatimah; Haerani Haerani; Arfiani Arfiani; Sumarni Sumarni; Hijrawati Hijrawati (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Exclusive breastfeeding for six months is crucial for infant growth, development, and health. However, in various regions, breastfeeding mothers still experience obstacles in breast milk production, resulting in suboptimal exclusive breastfeeding. One intervention that can be implemented to increase breast milk production is Oketani massage, a breast massage technique that stimulates the hormones prolactin and oxytocin. Purpose: This study aimed to determine the effect of Oketani massage on breast milk production in breastfeeding mothers in the Kassi-Kassi Community Health Center. Methods: The study used a quasi-experimental design with a pretest-posttest approach for the experimental and control groups. A sample of 28 respondents was divided into two groups (14 respondents with Oketani massage and 14 respondents without massage). Data were collected through observations of breast milk volume before and after the intervention, then analyzed using a t-test. Results: The results showed a significant difference in breast milk production before and after Oketani massage (p = 0.001). Average breast milk production increased in the group receiving Oketani massage compared to the control group. Conclusion: The study concluded that Oketani massage has a positive effect on increasing breast milk production in breastfeeding mothers. Healthcare workers are advised to teach and practice Oketani massage as a way to improve the success of exclusive breastfeeding.